FEATURES FOR OPTIMISING THE PROPERTIES OF COMPOSITE MATERIALS BASED ON ACRYLIC MONOMERS - Zolotov, S.; Trykoz, L.; Pustovoitova, O.; Kamchatna, S.; Orel, Ye. (Municipal economy of cities. Series: «Economy science», 2024)
Further development of research in the field of acrylic composites is aimed at creating modifiers with specified properties that will improve the characteristics of composites in specific application conditions; developing optimal ratios of composite components to ensure the required properties; developing universal mathematical models that will predict the properties of composites depending on the composition and curing conditions; searching for new applications for acrylic composites, such as industrial and civil engineering. Among all organic compounds, acrylic compounds demonstrate the highest rate of strength gain over a wide temperature range. This is due to the low activation energy of the polymerisation process of acrylic monomers, which is triggered by special initiators. Due to this feature, acrylic composites can cure even at low temperatures and gain high strength in a short time. However, despite the obvious advantages, there are a number of questions that require further research: how does the rate of strength gain and other properties of acrylic composites change at different temperatures? How does changing the ratio of composite components (pliable, filler, initiator) affect its properties? How does the curing process of acrylic composites work at the molecular level? Determining the answers to these questions will make it possible to select the optimal ratio of components to obtain a material with the required properties, control the rate of strength gain of the composite by changing the temperature and composition, and use acrylic composites in a wider range of temperature conditions. Thus, a deep understanding of the processes that occur during the curing of acrylic composites is a prerequisite for their effective use in various industries and construction . The aim of the study is to comprehensively study the properties of composite materials based on methyl methacrylate (MMA) for the purpose of their effective use. Research objectives: determination of the optimal temperature regime to achieve maximum composite strength in the shortest possible time (1.5-2 hours). Study the effect of various fillers and other components on the strength, durability and other properties of the material. Identification of effective ways to modify MMA to increase the strength of the composite. Development of methods for controlling the rate of strength gain to ensure optimal operation. Assessment of the durability of the adhesive bond under various operating conditions. Comparison of the properties of the developed composites with existing materials. The results of the study will make it possible to develop new, more efficient composite materials for repair work that will be widely used in construction, industry and other sectors.